2001
DOI: 10.1073/pnas.071548198
|View full text |Cite
|
Sign up to set email alerts
|

Control of HIV-1 viremia and protection from AIDS are associated with HLA-Bw4 homozygosity

Abstract: Certain HLA-B antigens have been associated with lack of progression to AIDS. HLA-B alleles can be divided into two mutually exclusive groups based on the expression of the molecular epitopes HLA-Bw4 and HLA-Bw6. Notably, in addition to its role in presenting viral peptides for immune recognition, the HLA-Bw4, but not HLA-Bw6, motif functions as a ligand for a natural killer cell inhibitory receptor (KIR). Here, we show that profound suppression of HIV-1 viremia is significantly associated with homozygosity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
3
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(166 citation statements)
references
References 41 publications
11
150
3
2
Order By: Relevance
“…Accordingly, some clinical data have confirmed that NK cell alloreactivity in the graft vs host (GVH) direction can reduce relapse rate and prolong OS after HSCT in patients with AML, 1,2,9 chronic myeloid leukemia (CML), 9,10 myelodysplastic syndrome (MDS) 9 and childhood acute lymphoid leukemia (ALL). 1 However, other studies have arrived at the opposite conclusion, particularly in unrelated donor HSCT (URD-HSCT), and have shown a deleterious effect of NK cell alloreactivity. 11 Natural killer cell alloreactivity (see above) was based on the KIR ligand mismatch model, also known as the ligandligand model.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Accordingly, some clinical data have confirmed that NK cell alloreactivity in the graft vs host (GVH) direction can reduce relapse rate and prolong OS after HSCT in patients with AML, 1,2,9 chronic myeloid leukemia (CML), 9,10 myelodysplastic syndrome (MDS) 9 and childhood acute lymphoid leukemia (ALL). 1 However, other studies have arrived at the opposite conclusion, particularly in unrelated donor HSCT (URD-HSCT), and have shown a deleterious effect of NK cell alloreactivity. 11 Natural killer cell alloreactivity (see above) was based on the KIR ligand mismatch model, also known as the ligandligand model.…”
Section: Introductionmentioning
confidence: 85%
“…Apart from alloreactive T cells, alloreactive natural killer (NK) cells also have an important role in the induction of a GVL effect after HSCT. 1,2 Natural killer cells possess the ability to kill cells that are undergoing tumorigenesis or infection by viruses or internal pathogens without previous stimulation. [3][4][5][6] NK cell function is determined by signaling through several receptor families, including activating and inhibitory killer-cell Ig-like receptors (KIRs).…”
Section: Introductionmentioning
confidence: 99%
“…Certain HLA supertypes, grouped according to Bpocket contact residues of the antigenic peptide recognized by HLA class I alleles, show modest associations with HIV transmission and with circulating set-point HIV concentration (viral load) 68 . Alleles of the HLA-Bw4 grouping, which comprises 40% of HLA-B alleles that share a seven-amino acid motif, are associated with long-term nonprogressors, although the study reporting this was controversial 65,67 . HLA-Bw4 alleles serve as a ligand for certain natural killer cell receptors encoded by the killer immunoglobulin receptor (KIR) gene complex on chromosome 19 (ref.…”
Section: Box 1 Attributable Risk Of Argsmentioning
confidence: 99%
“…Some provocative HLA associations involving functionally relevant HLA allele groupings with HIV infection and progression have also been reported 67,68 . Certain HLA supertypes, grouped according to Bpocket contact residues of the antigenic peptide recognized by HLA class I alleles, show modest associations with HIV transmission and with circulating set-point HIV concentration (viral load) 68 .…”
Section: Box 1 Attributable Risk Of Argsmentioning
confidence: 99%
“…The HLA-B alleles B*27 and B*57, which are commonly overrepresented in HICs [65][66][67], are members of the Bw4-80I group [68], suggesting that NK cells may contribute to establishing HIV control in these patients through direct cytolytic or non-cytolytic anti-HIV activities or by favouring the induction of an efficient CD8þ T cell response (see below) through optimal crosstalk with dendritic cells. Various reports suggest that NK cells from HICs have increased cytolytic and secretory potential [69][70][71], which may be associated with particular NK cell receptor profiles [69,71].…”
Section: Insights Into Immune Responses Conferring Spontaneous Contromentioning
confidence: 99%